THE USE OF DIGITAL STORYTELLING-BASED VISUAL PROMPTS IN SUPPORTING SPEAKING FLUENCY IN TENTH GRADE ENGLISH CLASSROOM AT SMAN 1 WELAHAN - Ulfa Fauziyah Widyawati Ulfa Fauziyah Widyawati; Zulfa Sakhiyya Zulfa Sakhiyya (BASIS (Bahasa dan Sastra Inggris), 2026)
Speaking fluency remains a major challenge for EFL learners in Indonesian senior high schools, particularly due to hesitation, low confidence, and difficulty in generating ideas during speaking activities. Therefore, this study aims to investigate the use of digital storytelling-based visual prompts in supporting speaking fluency among tenth-grade students at SMAN 1 Welahan. This research is grounded in the theory of speaking fluency proposed by Lopez et al. (2021), which emphasizes continuity of speech and reduced hesitation as key indicators, and is supported by dual coding theory by Paivio as discussed in Fatima (2023), which highlights the role of visual and verbal integration in enhancing language learning. This study employed a qualitative descriptive research design following Colorafi and Evans (2021) and Sandelowski (2021), focusing on classroom-based phenomena. Data were collected through classroom observation, students’ speaking performance, and questionnaires adapted from Asmawati (2023). The data were analyzed using descriptive qualitative techniques, including data reduction, categorization, and interpretation of patterns, as suggested by Sandelowski (2021). The research results were reported in both quantitative and qualitative forms, where students’ scores and questionnaire responses were presented in tables and percentages, while observational data were described narratively to explain students’ speaking behavior. The findings indicate that the use of digital storytelling-based visual prompts significantly supports students’ speaking fluency by reducing hesitation, improving confidence, and enhancing the continuity of speech. In addition, students showed positive perceptions toward the learning method, as it increased their motivation, participation, and engagement in speaking activities.